Aligning tarbiyyah education with digital age learning environments - Mhd. Sarif, Suhaimi; Ismail, Yusof; Yahya, Rohaziah (2023)
This study explores the alignment of traditional Islamic education with digital teaching and learning based on the principles of tarbiyyah. Five subject matter expert teachers from private Islamic primary schools in Malaysia were interviewed. Thematic data analysis was used to analyze the data. The findings revealed the challenges faced during the transition, the potential of online learning in enhancing learning and practices, and the strategies employed to integrate ethical digital citizenship within the traditional Islamic education. The teachers emphasized mindset change, incorporation of real-life examples, and collaborative online discussions to foster ethical considerations. They also highlighted the flexibility, wider reach, engaging multimedia, and continuous adaptation offered by online learning. The study suggests the importance of providing authentic prophetic exemplars and guidance for educators to effectively use online resources in line with tarbiyyah principles. The findings contribute to enhancing Islamic education learning, promoting moral character, and nurturing morally conscious individuals. The study highlights the need to align Islamic education with the digital age and foster a dynamic and engaging learning environment that upholds tarbiyyah principles.